2018
DOI: 10.4183/aeb.2018.76
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency, A Noninvasive Marker of Steatohepatitis in Patients with Obesity and Biopsy Proven Nonalcoholic Fatty Liver Disease

Abstract: Context. Nonalcoholic fatty liver disease (NAFLD) includes simple steatosis, steatohepatitis (NASH) which can evolve with progressive fibrosis, cirrhosis and hepatocellular carcinoma. As liver biopsy cannot be used as a screening method, noninvasive markers are needed.Objective. The aim of this study was to test if there is a significant association between vitamin D deficit and the severity of NAFLD.Design. The patients were divided into two groups (vitamin D insufficiency/deficiency) and statistical analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…Despite obtaining information only from a quite small number of patients, our data are consistent with other recently published results that showed that steatosis is present in an important number of T2DM patients and it was positively correlated with liver fibrosis (23)(24).…”
Section: Discussionsupporting
confidence: 92%
“…Despite obtaining information only from a quite small number of patients, our data are consistent with other recently published results that showed that steatosis is present in an important number of T2DM patients and it was positively correlated with liver fibrosis (23)(24).…”
Section: Discussionsupporting
confidence: 92%
“…The association between vitamin D deficiency in adulthood and chronic liver diseases (CLD) ( 40 ), including cirrhosis ( 41 ), non-alcoholic fatty liver disease (NAFLD, recently been proposed to rename as metabolic-associated fatty liver disease [MAFLD) ( 42 )] ( 43 45 ), and non-alcoholic steatohepatitis (NASH) ( 44 , 45 ), have been identified in many cross-sectional studies. Stokes et al.…”
Section: Discussionmentioning
confidence: 99%
“…While the liver is mainly affected, a large portion of the gastrointestinal system is inhibited by the presence of various biomarkers that disrupt chemical and endocrine functionality. These biomarkers consist of, but are not limited to, cholesteryl ester transfer protein (CETP) [ 55 ], neurotensin (NT) [ 56 ], and vitamin D [ 57 ]. CETP accompanies NAFLD progression through metabolic liver inflammation.…”
Section: Consequences Of Bariatric Surgerymentioning
confidence: 99%
“…High levels of NT have been associated with high rates of NAFLD, cardiovascular disease, T2DM, and obesity. Insufficient or deficient vitamin D levels are indicative of NAFLD progression in association with fibrinogen levels, PCR levels, and T2DM [ 57 ].…”
Section: Consequences Of Bariatric Surgerymentioning
confidence: 99%